2018
DOI: 10.3390/min8120585
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular and Intracellular Biomineralization Induced by Bacillus licheniformis DB1-9 at Different Mg/Ca Molar Ratios

Abstract: Biomineralization has become a research hotspot and attracted widespread attention in the field of carbonate sedimentology. In this study, precipitation of carbonate minerals was induced by Bacillus licheniformis DB1-9 bacteria, (identity confirmed with its phylogenetic tree), to further explore the biomineralization mechanisms. During experiments, lasting up to 24 days with varying Mg/Ca molar ratios and regular monitoring of conditions, ammonia and carbonic anhydrase are released by the bacteria, resulting i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 90 publications
7
24
1
Order By: Relevance
“…The adsorption peaks at 712, 875 and 1421 cm −1 are the characteristic peaks of calcite, and the characteristic peaks of vaterite are at 745, 870 and 1421 cm −1 [2,7]. In addition, the peaks at 700, 765, 872, 1064, 1401 and 1480 cm −1 record the presence of monohydrocalcite [7,58]. Characteristic peaks of struvite include the H-O-H group for water molecules at 1656 cm −1 ; the symmetrical and asymmetrical bending vibration of N-H (NH + 4 ) at 1609 and 1439 cm −1 ; the asymmetrical stretching vibration of PO 3− 4 at 1003.79 and 571.78 cm −1 ; the symmetrical bending vibration of PO 3− 4 at 453.16 cm −1 ; the hydrogen bond between waters at 762.4 cm −1 and the hydrogen bond between ammonium and water at 886.70 cm −1 [22,32].…”
Section: Ftir Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…The adsorption peaks at 712, 875 and 1421 cm −1 are the characteristic peaks of calcite, and the characteristic peaks of vaterite are at 745, 870 and 1421 cm −1 [2,7]. In addition, the peaks at 700, 765, 872, 1064, 1401 and 1480 cm −1 record the presence of monohydrocalcite [7,58]. Characteristic peaks of struvite include the H-O-H group for water molecules at 1656 cm −1 ; the symmetrical and asymmetrical bending vibration of N-H (NH + 4 ) at 1609 and 1439 cm −1 ; the asymmetrical stretching vibration of PO 3− 4 at 1003.79 and 571.78 cm −1 ; the symmetrical bending vibration of PO 3− 4 at 453.16 cm −1 ; the hydrogen bond between waters at 762.4 cm −1 and the hydrogen bond between ammonium and water at 886.70 cm −1 [22,32].…”
Section: Ftir Analysesmentioning
confidence: 98%
“…CA activity then showed a slight decline from 60 h to 156 h. From Figure 1b, it can be concluded that there was still a large amount of CA in the fluid even during the decline stage of ZW123 bacteria (Figure 1a). CA can catalyze the hydration of carbon dioxide to release bicarbonate and carbonate ions [32,58]. The concentration of bicarbonate increased from 0.02 mol/L to 0.036 mol/L in the first 48 h, declined from 0.036 mol/L to 0.0163 mol/L in the time range of 48-96 h, then almost remained stable until 156 h. Coinciding with the decline of the bicarbonate, the presence of carbonate was first detected at 72 h; the concentration of carbonate then increased from 0.007 mol/L to 0.019 mol/L in the time range of 72-96 h, and then remained nearly stable.…”
Section: Physicochemical Parameters Of the Liquid Medium Inoculated Wmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the decrease of nucleation energy caused by the functional groups on the bacterial surface could induce the mineralization process more easily [48]. Additionally, organic matters secreted by the bacteria played a key role in the regulation of the mineral morphology and phases [45,49,50]. A number of studies have confirmed that some amino acids have an ability to promote the formation of vaterite crystals [51][52][53][54].…”
Section: Extracellular Biomineralsmentioning
confidence: 99%
“…The ion adsorption ability of bacteria is mainly caused by the surface charge and zeta-potential [71]. It has been reported that different functional groups on the surface of bacteria such as hydroxyl, carboxyl, phosphoryl, and amide groups can contribute to this nucleation process [48,49]. In a previous study, it was found that some bacteria can preferentially adsorb Mg 2+ on their membranes to induce the formation of dolomite, and others adsorb Ca 2+ to induce calcite [29].…”
Section: Intracellular Amorphous Inclusionsmentioning
confidence: 99%